2014
DOI: 10.1111/ans.12513
|View full text |Cite
|
Sign up to set email alerts
|

Dupuytren's contracture: an analysis of outcomes of percutaneous needle fasciotomy versus open fasciectomy

Abstract: The OF and PNF procedures provide comparable deformity correction for uncomplicated primary Dupuytren's disease in the immediate perioperative period. The reduced side effect profile of PNF should prompt surgeons to consider incorporating it in their practice for the first-line management of uncomplicated primary Dupuytren's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…71,72 Of the surgery non-randomised studies, one was conducted in several countries, 73 one in the UK, 74 one in Brazil, 57 one in the USA 75 and one in Australia. 76 Nine of the collagenase case series were conducted in the USA 48,77,81,83,[85][86][87][88][89] two in Australia, 78,79 one in the UK, 91 one in Spain, 84 one in several countries, 90 and the remaining one did not report this information. 63 The non-randomised studies comparing collagenase with surgery enrolled and analysed a total of 105 participants.…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…71,72 Of the surgery non-randomised studies, one was conducted in several countries, 73 one in the UK, 74 one in Brazil, 57 one in the USA 75 and one in Australia. 76 Nine of the collagenase case series were conducted in the USA 48,77,81,83,[85][86][87][88][89] two in Australia, 78,79 one in the UK, 91 one in Spain, 84 one in several countries, 90 and the remaining one did not report this information. 63 The non-randomised studies comparing collagenase with surgery enrolled and analysed a total of 105 participants.…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
“…The two non-randomised studies comparing collagenase with surgery 71,72 and the five non-randomised studies comparing various surgical procedures 44,57,[73][74][75][76] were published in full. Three studies collected data prospectively 72,74,75 and three retrospectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The functional outcomes have usually been documented through physical measurements and through patient-reported outcome questionnaires [17]. Patient satisfaction with the outcome or with the treatment for DD, evaluated with different methods has also been reported in several studies [17,[20][21][22][23][24][25]. However, previous research has concluded that patient satisfaction is a multidimensional concept that can be difficult to capture [26][27][28][29][30], and that it is associated with structure and process aspects of care [28].…”
Section: Introductionmentioning
confidence: 99%
“…the development of new DD tissue in the operated area (1). Despite possible drawbacks of surgery, several studies report high overall patient satisfaction or satisfaction with the procedure (15,17,(20)(21)(22)(23)(24). After fasciectomy, patients also report improved quality of life (25).…”
Section: Introductionmentioning
confidence: 99%